Analisis Implikatur Pada Teks Editorial Media Indonesia Oktober 2021 dan Rekomendasi dalam Pembelajaran Teks Editorial Di Kelas XII SMA - Aulia, Kartika; Suprihatin, Dewi; Setiawan, Hendra (Peneliti.net, 2024)
This study aims to analyze the form and function of editorial text implicature and its use as teaching material in class XII SMA. This research is a qualitative descriptive study with the subject of the editorial text of Media Indonesia and the object of the text structure, form and function of the implicature. In this study, data collection was carried out using note-taking techniques. Then the data is categorized and performs discourse analysis. From the research that has been done, it is found that 26 editorial texts are included in conventional implicature forms. Then found 117 implicature function data consisting of 44 representative implicature function data, 56 directive implicature function data, fifteen expressive implicature function data, and two commissive implicature function data. The results of the research on the forms and functions of the implicatures of the editorial text of the October 2021 edition of Media Indonesia and recommendations for teaching editorial texts in class XII SMA are used as teaching materials in the form of handouts.